ON CALCULATION OF VIBRATION AND NOISE SPECTRA IN PROCESSING BOX BODIES WITH BALL-POINT REINFORCER - Andrey N. LESHCHENKO (Advanced Engineering Research)
Calculation of the vibration and noise spectra in processing box bodies with the ball-point reinforcer and theoretical research results of vibro-acoustic performance of this kind of treatment are presented. Dependences for the vibro-speed and acoustic power levels are detected. It is established that abatement of noise can be achieved only by decreasing the vibrational energy loss factor.